Kajian Yuridis Perlindungan Hukum Bagi Pemberi Gadai Dalam Perjanjian Gadai Di Pegadaian Cabang Ngupasan Kota Yogyakarta - Goreti Beto Tapobali, Maria; Budi Pratiwi, Wiwin (Private Law, 2024)
PT Pegadaian Ngupasan Branch in Yogyakarta City in providing money loans can make an agreement with the pawn giver, the pawn giver must have collateral. Without bringing a collateral object a pawn giver will not get the loan money, so the existence of a collateral object is a condition of borrowing money at PT Pegadaian Ngupasan Branch. This research was conducted at PT Pegadaian Ngupasan Branch which aims to determine and analyze the form of legal protection provided by PT Pegadaian Ngupasan Branch Yogyakarta City to the pawn giver in terms of making a pawn agreement and knowing and analyzing the efforts made by PT Pegadaian Ngupasan Branch Yogyakarta City if there is a pawn giver who defaults on the pawn agreement. This research uses normative legal research and empirical juridical approaches. The data source used is secondary by collecting data from document studies and field research based on interview guidelines, then analyzed using qualitative descriptive methods. Respondents in this study were the head of the ngupasan branch pawnshop and two pawnbrokers. The results showed that 1) Legal protection of the pawn giver in general is preventive legal protection, PT Pegadaian as a pawn holder has an obligation to secure and maintain collateral and repressive legal protection, if a dispute occurs, the dispute is first resolved by deliberation to reach consensus through the handling of internal guidance. 2) The action taken by PT Pegadaian Ngupasan Branch if there is a pawn giver who defaults on the pawn agreement is to notify the pawn giver that the credit payment is due by contacting or calling the pawn giver three times, in accordance with the stipulated provisions.